DNA damage caused by chemotherapy has duality, and traditional Chinese medicine may be a better choice to reduce its toxicity - Bai, Bufan; Ma, Yingrui; Liu, Deng; Zhang, Yifei; Zhang, Weihong; Shi, Rong; Zhou, Qianmei (Frontiers in Pharmacology, 2024)
Background：DNA damage induced by chemotherapy has duality. It affects the efficacy of chemotherapy and constrains its application. An increasing number of studies have shown that traditional Chinese medicine (TCM) is highly effective in reducing side-effects induced by chemotherapy due to its natural, non-toxic and many sourced from food. Recent advancements have demonstrated survival rates are improved attributable to effective chemotherapy. DNA damage is the principal mechanism underlying chemotherapy. However, not all instances of DNA damage are beneficial. Chemotherapy induces DNA damage in normal cells, leading to side effects. It affects the efficacy of chemotherapy and constrains its application. Objectives: This review aims to summarize the dual nature of DNA damage induced by chemotherapy and explore how TCM can mitigate chemotherapy-induced side effects. Results: The review summarized the latest research progress in DNA damage caused by chemotherapy and the effect of alleviating side effects by TCM. It focused on advantages and disadvantages of chemotherapy, the mechanism of drugs and providing insights for rational and effective clinical treatment and serving as a basis for experiment. In this review, we described the mechanisms of DNA damage, associated chemotherapeutics, and their toxicity. Furthermore, we explored Chinese herb that can alleviate chemotherapy-induced side-effects. Conclusions: We highlight key mechanisms of DNA damage caused by chemotherapeutics and discuss specific TCM herbs that have shown potential in reducing these side effects. It can provide reference for clinical and basic research.